2017
DOI: 10.1210/en.2016-1929
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification of Basic Helix–Loop–Helix and NF-1 Motifs Underlying GR Binding Sites in Male Rat Hippocampus

Abstract: Glucocorticoids regulate hippocampal function in part by modulating gene expression through the glucocorticoid receptor (GR). GR binding is highly cell type specific, directed to accessible chromatin regions established during tissue differentiation. Distinct classes of GR binding sites are dependent on the activity of additional signal-activated transcription factors that prime chromatin toward context-specific organization. We hypothesized a stress context dependency for GR binding in hippocampus as a conseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(52 citation statements)
references
References 108 publications
(109 reference statements)
2
50
0
Order By: Relevance
“…In view of their very different effects in the hippocampus, MR and GR should have unique target genes, and this assumption indeed recently has been materialized in three independent studies [31,32,41]. A unique signature of MR binding to DNA loci was discovered and found associated with the NeuroD transcription factor [33].…”
Section: Molecular Mechanisms Of Mr-/gr-mediated Actionsmentioning
confidence: 98%
See 1 more Smart Citation
“…In view of their very different effects in the hippocampus, MR and GR should have unique target genes, and this assumption indeed recently has been materialized in three independent studies [31,32,41]. A unique signature of MR binding to DNA loci was discovered and found associated with the NeuroD transcription factor [33].…”
Section: Molecular Mechanisms Of Mr-/gr-mediated Actionsmentioning
confidence: 98%
“…Recent studies that evaluated MR and GR binding to the DNA in the hippocampus indicate that the receptors interact with the DNA via their-homologous-DNA-binding domains [31][32][33]. MR and GR share 96% homology in their DNAbinding domain, and both recognize the same "GRE" sequence in the DNA to which they bind as homo-or heterodimers.…”
Section: Molecular Mechanisms Of Mr-/gr-mediated Actionsmentioning
confidence: 99%
“…The first studies to suggest nuclear hormone receptor interactions with chromatin were reported as early as the 1960s. 28 Additionally, ChIP-Seq has enabled the genome-wide assessment of how binding profiles for GR, ER, PR and AR are highly celltype specific and subject to alteration with changing environmental conditions, [29][30][31][32][33][34][35][36] as well as being dependent upon other regulatory proteins such as AP-1 and FoxA1. Figure 1 shows ChIP-Seq data from rat hippocampal tissue, highlighting a selection of the GR binding events induced by acute stress and exogenous corticosterone treatment.…”
Section: S Teroid Recep Tor B Ind Ing and Chromatin Acce Ss Ib Ilit Ymentioning
confidence: 99%
“…Figure 1 shows ChIP-Seq data from rat hippocampal tissue, highlighting a selection of the GR binding events induced by acute stress and exogenous corticosterone treatment. 28 Additionally, ChIP-Seq has enabled the genome-wide assessment of how binding profiles for GR, ER, PR and AR are highly celltype specific and subject to alteration with changing environmental conditions, [29][30][31][32][33][34][35][36] as well as being dependent upon other regulatory proteins such as AP-1 and FoxA1. 30,37 ChIP-Seq has revealed insights into the loss of protein-DNA associations occurring in disease states, such as cancer, increasing our understanding of disease development and potentially leading to the development of more specific therapies.…”
Section: S Teroid Recep Tor B Ind Ing and Chromatin Acce Ss Ib Ilit Ymentioning
confidence: 99%
See 1 more Smart Citation